Massachusetts Food Access Index: A Pilot Method for Assessing Food Access in the Commonwealth. - Fanous, Jamie.; Habeeb, Noah.; Matthews, Caitlin.; Raczka, Alexandra. (Tufts University. Tisch Library., 2018)
2016 M.A. in Urban and Environmental Policy and Planning Field Project. Client: Metropolitan Area Planning Council.